Integration of Environmental Education in Geography Learning to Improve Ecological Attitudes and Knowledge of Senior High School Students - Liza Lu'aiatun Niswa; Juhadi Juhadi; Ananto Aji; Purnomo Adi Saputro (JPG (Jurnal Pendidikan Geografi), 2025)
This study aims to describe the planning, implementation, and evaluation of geography learning in shaping environmental awareness attitudes and knowledge in class XI students at SMA Negeri 2 Pekalongan. Geography learning has a strategic role in instilling environmental awareness values through a contextual approach in accordance with the direction of the Merdeka Curriculum. This study used a descriptive quantitative approach with 134 students randomly selected from four classes. Data was collected through diagnostic assessments, attitude questionnaires, knowledge tests, and skill observations, which have been tested for validity and reliability. The results showed that geography lesson planning has integrated environmental values, although it is not always explicit in the learning objectives. Learning implementation through local case discussion and thematic reflection succeeded in increasing students' awareness of environmental issues. The evaluation shows that students have high environmental knowledge (mean score 22.33 out of 25), positive attitude towards the environment (mean 33.93 out of 40), and environmental care skills in moderate to high category (mean 30.00 out of 44). This finding confirms that geography learning is designed contextually and participatively can shape the character of students who care about the environment. This research recommends strengthening institutional support and developing sustainable learning strategies to strengthen ecological character education in schools.